Imagination and Meticulousness: Haggadah and Halakhah in Judaism and Christian Preaching (Homiletic, 2009)
The paper demonstrates how Christian preaching can learn from Jewish preaching and Jewish (esp. Rabbinic) Scriptural interpretation. The rabbinic concepts of Haggadah and Halakhah can justify a new enthusiasm for the creative and precise, imaginative and meticulous exploration of the biblical word in Christian sermons.